Planning and Preparation of The Operational Budget of The Investment Service Department - Lisa Arisa; Diah Yuningsih (Journal of Applied Business, Taxation and Economics Research, 2023)
The aim of this study is to describe procedure of planning and preparation operational budget on investment department in Serang City. The method used in this research is a qualitative descriptive research method. The techniques used in data collection where the data sources obtained are primary and secondary data. Serang City Investment and One-Stop Integrated Services Service As an institution or agency engaged in licensing and services, it really needs budget planning procedures, with budget planning procedures it can help minimize the occurrence of a budget preparation at the One-Stop Investment and Services Office of Serang City From the results of the discussion, the Regional Apparatus Organizational Budget Planning Procedure Case Study at the Serang City Investment and One-Stop Service Office is in accordance with established procedures so that it runs well and according to procedures.